The immunological profile of the skin in DRESS and SJS/TEN reactions to first-line tuberculosis drugs in HIV-infected patients - Chimbetete, Tafadzwa (Department of Medicine, 2026)
Introduction: A greater incidence of severe cutaneous adverse drug reaction (SCAR) such as Drug Reaction with Eosinophilia Systemic Symptoms (DRESS) and Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) occur among HIV-infected patients. We sought to characterize the immunohistological phenotype of the skin in these reactions to first-line TB drugs in HIV-infected cases, with a hypothesis that a possible depletion of T-regulatory cells (Tregs) and increased infiltration of effector cells may contribute to SCAR in the context of HIV. Participants and Methods: HIV cases with validated SCAR phenotypes (probable or definite) and confirmed reactions to either one or multiple first-line anti-TB (FLTB) drugs were chosen (n=20). These cases were matched against controls of HIV-uninfected patients who develop SCAR (n=6). Immunohistochemistry assays were carried out with the following antibodies: CD3, CD4, CD8, CD45RO and FOXP3. Positive cells were normalized to the number of CD3+ cells present. Results: Infiltrated immunoreactive T cells in SCAR were mainly found in the dermis. Dermal and epidermal CD4+ T-cells (and CD4+/CD8+ ratios) were lower in HIV-infected versus uninfected DRESS; p < 0.001 and p = 0.004, respectively. In contrast, no difference in dermal CD4+FOXP3+ Tregs were found in HIV-infected versus uninfected DRESS; median (IQR) CD4+FOXP3+ Tregs: [10 (0 - 30) cells/mm2 versus 4 (3 - 8) cells/mm2, p = 0.325]. HIV-infected SCAR patients clinically reacting to more than one FLTB drug (n=4) showed increased dermal CD4+ T-cells compared to single drug reactors (n=12), [32 (23 - 41) versus 15 (11 - 20) cells/high-powered field, p = 0.03]. This was associated with increased dermal CD4+FOXP3+ Tregs in multiple drug reactors, [39 (36- 48) versus 10 (1-22), p = 0.02] Conclusion: HIV-infected and uninfected SCAR was associated with an increased infiltration of cytotoxic CD8+ T-cells compared to normal skin, displaying their role as key mediators of tissue damage. CD4+ T-cells were decreased in HIV-infected SCAR, in line with known HIV pathology and higher dermal infiltrates were associated with risk for reactivity to multiple unrelated medications. While inter-individual variation was high, dermal Tregs were in fact increased in HIV-infected DRESS, and this requires further research to understand their role and any possible impact on lower SCAR mortality amongst HIV-infected patients.